Analisa Algoritma Ciphers Transposition: Study Literature - Juwita Artanti Kusumaningtyas (Universitas Ngudi Waluyo, 2018)
Technological developments allow the sending and storage of data can be done quickly, easily, practically, and safely. One security used uses cryptographic techniques. Cryptography is a technique of converting original text (plaintext) into secret text (ciphertext) using cryptographic algorithms (ciphers) or what is called the encryption process. The decryption process is the process of converting data encoded into original data. One of the cryptographic algorithms is the Cipher Transposition Algorithm. The analysis aims to determine the characteristics and application of the Transposition Cipher. The method used in this study by means of Study Literature, analyzes previous research from journals related to the Transposition Cipher Algorithm. The results are in the form of a view using the study literature method and knowing the characteristics and application of the Cipher Transposition algorithm and analyzing trends in previous studies.Â Kata Kunci : Cryptography, Algorithms, Cipher Transposition, Study literature